INTEGRATION OF OVERALL EQUIPMENT EFFECTIVENESS (OEE) AND RELIABILITY METHOD FOR MEASURING MACHINE EFFECTIVENESS - Abdul Samat, H.; Kamaruddin, S.; Abdul Azid, I. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Maintenance is an important process in a manufacturing system. Thus it should be conducted and measured effectively to ensure performance efficiency. A variety of studies have been conducted on maintenance as affected by factors such as productivity, cost, employee skills, resource utilisation, equipment, processes, and maintenance task planning and scheduling [1,2]. According to Coetzee [3], equipment is the most significant factor affecting maintenance performance because it is directly influenced by maintenance activities. This paper proposes an equipment performance and reliability (EPR) model for measuring maintenance performance based on machine effectiveness. The model is developed in four phases, using Pareto analysis for machine selection, and failure mode and effect analysis (FMEA) for failure analysis processes. Machine effectiveness is measured using the integration of overall equipment effectiveness and the reliability principle. The result is interpreted in terms of maintenance effectiveness, using five health index levels as bases. The model is implemented in a semiconductor company, and the outcomes confirm the practicality of the EPR model as it helps companies to measure maintenance effectiveness. AFRIKAANSE OPSOMMING: Instandhouding is